Ostarine Avoids Masseter Atrophy Caused by Changes in the Diet Consistency - Shindo, João Vitor Tadashi Cosin; Bellini, Júlia Pedrozo; Biguetti, Cláudia Cristina; Couto, Maira; Pomini, Karina Torres; Matsumoto, Mariza Akemi [UNESP]; German, Iris Santos; Andreo, Jesus Carlos; Buchaim, Rogério Leone; Shinohara, André Luís (My University, 2022)
Introduction: modern eating habits, which softer and processed foods predominate in, requiring less effort to chew and have been correlated with an increase in the incidence of malocclusion and problems in the temporomandibular joint (TMJ) also, reducing the cross-sectional area (CSA). This vital muscle fiber variable indicates muscle function and strength. Selective androgen receptor modulators (SARMs) were developed to treat muscular and skeletal system problems to replace traditional androgens. This study aimed to verify if the use of ostarine associated with a soft-diet could exert the same anabolic and anti-catabolic effects on the masseter muscle described in the literature. Material and Methods: fifteen six-months age C57BL/WT mice were used and divided into three groups and fed on either a solid (Control group - CG) or a soft-diet (Soft Diet Control Group - SDCG) with and without ostarine (Ostarine Group - OG). Results: as a result, the soft-diet (SDCG) showed a lower median than the hard-diet (CG), but without statistical differences. However, the OG associated with a soft-diet presented a higher CSA than the SDCG with a statistical difference. Conclusions: although there was no statistical difference between CG and SDCG group, slight atrophy occurred, and the use of ostarine (OG) reversed this process, becoming equal to the CG with a hard-diet.
Keywords: Androgens; Atrophy; Diet Consistency; Masseter Muscle; Nutrition